Digital Microfluidics-Powered Real-Time Monitoring of Isothermal DNA Amplification of Cancer Biomarker - Coelho, Beatriz Jorge (2022)
LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy?i4HB. Additional funding was received from FCT under the scope of the project reference LA/P/0037/2020, Beatriz J. Coelho and grant COVID/BD/152453/2022. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.